The association between disability and cognitive impairment in an elderly Tanzanian population. Issue 1 (March 2015) - Dotchin, Catherine L.; Paddick, Stella-Maria; Gray, William K.; Kisoli, Aloyce; Orega, Golda; Longdon, Anna R.; Chaote, Paul; Dewhurst, Felicity; Dewhurst, Matthew; Walker, Richard W.
Abstract: Cognitive impairment is thought to be a major cause of disability worldwide, though data from sub-Saharan Africa (SSA) are sparse. This study aimed to investigate the association between cognitive impairment and disability in a cohort of community-dwelling older adults living in Tanzania. The study cohort of 296 people aged 70 years and over was recruited as part of a dementia prevalence study. Subjects were diagnosed as having dementia or mild cognitive impairment according to the DSM-IV criteria. Disability level was assessed according to the WHO Disability Assessment Schedule, version 2.0 (WHODAS). A higher WHODAS score indicates greater disability. The median WHODAS in the background population was 25.0; in those with dementia and in those with mild cognitive impairment, 72 of 78 (92.3%) and 41 of 46 (89.1%), respectively, had a WHODAS score above this level. The presence of dementia, mild cognitive impairment, hearing impairment, being unable to walk without an aid and not having attended school were independent predictors of having a WHODAS score above 25.0, though age and gender were not. In summary, cognitive impairment is a significant predictor of disability in elderly Tanzanians. Screening for early signs of cognitive decline would allow management strategies to be put in place that may reduce the associated disability burden.